PENGARUH KARAKTERISTIK DEMOGRAFI TERHADAP KEJADIAN STUNTING PADA BALITA DI PROVINSI SULAWESI BARAT - Dwi Ardian; Efri Diah Utami (Politeknik Statistika STIS, 2020)
The government has a target of improving nutrition in in sustainable development (SDGs). One of nutritional problem is stunting. Stunting is a condition of failure to thrive in children under five due to chronic malnutrition. The high prevalence of stunting causes major problems in various sectors. Although in 2018 there was a significant decline from 37.2 percent (2013) to 30.8 percent (2018), but it is still far from WHO standards, which is below 20 percent. In addition, inequality between regions is very large. The prevalence of stunting in DKI Jakarta is already 17.6 percent, while most other regions are still above 30 percent. West Sulawesi is one of the provinces with the highest prevalence of stunting (41.6 percent), even for the very short toddler category, West Sulawesi is the highest in Indonesia. This study aims to study the effect of demographic characteristics on the incidence of stunting in children under five in West Sulawesi. The data used are the results of the 2018 basic health research (Riskesdas 2018). The analytical method uses binary logistic regression which concludes that mother’s education, father's education, history of maternal pregnancy check up, history of TTD consumption during maternal pregnancy, and maternal age at birth have a significant influence on the incidence of stunting in toddlers. These results indicate that household knowledge and awareness are the main steps in preventing the prevention of stunting.